2023
DOI: 10.1093/qjmed/hcad147
|View full text |Cite
|
Sign up to set email alerts
|

New application of saline contrast-enhanced electrical impedance tomography method for right ventriculography besides lung perfusion: detection of right-to-left intracardiac shunt

Abstract: Aim Saline contrast-enhanced electrical impedance tomography (EIT) has been used to identify the respiratory failure etiologies through assessment of regional lung perfusion at the bedside. In this study, we introduce a novel approach to detect right-to-left intracardiac shunt based on the center of heart (CoH) parameter determined from the early phase of impedance-time curve after saline bolus injection. Methods and result T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…NaCl solution) in the respiratory depression state enhance impedance changes in the perfused area and perform EIT imaging [12,13]. The results of the comparative study showed a good correlation between the results obtained by this method and PET and SPECT in the detection of pulmonary perfusion function [14], as well as a superiority in the ability to identify acute pulmonary embolism [15], which led to the initial clinical acceptance of the method. However, this method not only has the shortcomings of being invasive and inconvenient to operate, but also fails to achieve continuous monitoring of pulmonary perfusion, and thus cannot be used for the monitoring and warning of pulmonary embolism.…”
Section: Introductionmentioning
confidence: 88%
“…NaCl solution) in the respiratory depression state enhance impedance changes in the perfused area and perform EIT imaging [12,13]. The results of the comparative study showed a good correlation between the results obtained by this method and PET and SPECT in the detection of pulmonary perfusion function [14], as well as a superiority in the ability to identify acute pulmonary embolism [15], which led to the initial clinical acceptance of the method. However, this method not only has the shortcomings of being invasive and inconvenient to operate, but also fails to achieve continuous monitoring of pulmonary perfusion, and thus cannot be used for the monitoring and warning of pulmonary embolism.…”
Section: Introductionmentioning
confidence: 88%